Perbandingan Performa Sensor DHT11, DHT22, dan 808H5V5 terhadap Pengukuran Kelembapan Udara Berbasis Internet Of Things - Jumawal; Harianto; Mahpuz; Muhammad Wasil (Infotek: Jurnal Informatika dan Teknologi, 2026)
This study aims to compare the performance of three air humidity sensors—DHT11, DHT22, and 808H5V5—integrated with an ESP8266 microcontroller based on the Internet of Things (IoT). The system was designed to monitor air humidity in real-time through a web server that displays measurement data from the three sensors along with a hygrometer as a reference. Data collection was conducted every hour from 08:00 to 17:00 under stable environmental conditions. The results show that the DHT22 sensor achieved the highest accuracy, with an average deviation of 0.3% compared to the hygrometer. The 808H5V5 sensor demonstrated the fastest response with an average deviation of 0.6%, while the DHT11 sensor had an average deviation of 1.1% and slower response time. All three sensors successfully transmitted real-time data through an accessible web server. Based on these findings, the DHT22 is recommended as the most accurate sensor for IoT-based humidity monitoring systems, while the DHT11 and 808H5V5 remain suitable for simpler applications requiring moderate precision and lower cost.